2022
DOI: 10.1186/s12879-022-07501-4
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of holding urine as a behavioral risk factor for UTI in women and reasons for delayed voiding

Abstract: Background Women of reproductive age group have greater predilection to urinary tract infections (UTI). Various risk factors increase the prevalence in women. Emergence of multidrug resistant uropathogens make clinical management of UTI challenging. Here we assess holding of urine as risk factor of UTI in women and reasons for delayed voiding. We also investigate the relationship between frequency of UTIs and overall behavioural features, menstrual hygiene and attitude of women towards their ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“… 24 This study showed the link between holding urine on several occasions and UTIs and supported the conclusions drawn by several other observational studies, stating “any delay in voiding increases the risk of UTI in adolescents and young adult women”. 25 , 26 The finding supports the hypothesis that if a woman delays urination by holding urine regularly for various reasons, it increases her chances of suffering from UTI multifold. The finding suggests the timely voiding or urination in peri- and postmenopausal women to prevent UTIs, as indicated in previously published guidelines.…”
Section: Discussionsupporting
confidence: 75%
“… 24 This study showed the link between holding urine on several occasions and UTIs and supported the conclusions drawn by several other observational studies, stating “any delay in voiding increases the risk of UTI in adolescents and young adult women”. 25 , 26 The finding supports the hypothesis that if a woman delays urination by holding urine regularly for various reasons, it increases her chances of suffering from UTI multifold. The finding suggests the timely voiding or urination in peri- and postmenopausal women to prevent UTIs, as indicated in previously published guidelines.…”
Section: Discussionsupporting
confidence: 75%
“…Since then, many studies have demonstrated a possible association between menstrual hygiene management practices and urinary or reproductive tract infections [ 3 , 12 , 13 ]. In a previous study, approximately 40% of women with UTI self-reported that they had UTI signs after menstruation [ 4 ]. Contaminated vaginal discharges and/or the changed vaginal microbiome during the menstruation period may underlie these findings [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Urinary tract infection (UTI) is known to have various risk factors and predisposing conditions, such as diabetes mellitus, sexual intercourse, menstrual hygiene, holding urine for a long time, dehydration, and urinary incontinence [1][2][3][4][5][6]. UTI is known to occur several times more frequently in women than in men, with a supposed lifetime incidence of more than 50% in women [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Holding urine for a long time has proven to be an important risk factor, and among the different reasons for holding urine, holding due to the poor sanitary condition of public toilets was the most common. The higher frequency of self-reported UTIs is related to the holding of urine, behavioral features, and attitudes of women [ 22 ]. Notably, the use of Western toilets and exposure to unsanitary public facilities were also significantly associated with increased UTI prevalence [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
“…The synthesis of these findings points to an urgent need for multifaceted public health initiatives and clinical interventions that prioritize sanitation, hydration, hygiene, and awareness of sexual health practices [ 22 ]. Such initiatives are critical in not only preventing UTIs but also in mitigating their broader impacts on women's health and well-being.…”
Section: Reviewmentioning
confidence: 99%